2016
DOI: 10.1371/journal.pgen.1006020
|View full text |Cite
|
Sign up to set email alerts
|

The Occurrence of the Holometabolous Pupal Stage Requires the Interaction between E93, Krüppel-Homolog 1 and Broad-Complex

Abstract: Complete metamorphosis (Holometaboly) is a key innovation that underlies the spectacular success of holometabolous insects. Phylogenetic analyses indicate that Holometabola form a monophyletic group that evolved from ancestors exhibiting hemimetabolous development (Hemimetaboly). However, the nature of the changes underlying this crucial transition, including the occurrence of the holometabolan-specific pupal stage, is poorly understood. Using the holometabolous beetle Tribolium castaneum as a model insect, he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
121
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(143 citation statements)
references
References 59 publications
14
121
1
2
Order By: Relevance
“…E93 gene expression during the pupal stage functions as an adult specifier and plays a key role in inducing programmed cell death necessary for tissue remodeling (30)(31)(32)(33). Genetic studies have revealed that during the larval stage, JH suppresses E93 expression to prevent larvae from undergoing precocious metamorphosis to adults (34)(35)(36). In the present study, we clarified the molecular mechanism underlying the repression of E93 by JH.…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…E93 gene expression during the pupal stage functions as an adult specifier and plays a key role in inducing programmed cell death necessary for tissue remodeling (30)(31)(32)(33). Genetic studies have revealed that during the larval stage, JH suppresses E93 expression to prevent larvae from undergoing precocious metamorphosis to adults (34)(35)(36). In the present study, we clarified the molecular mechanism underlying the repression of E93 by JH.…”
Section: Discussionmentioning
confidence: 78%
“…These residues in Kr-h1 are highly conserved in other insect species (15), suggesting that Kr-h1 homologs in other insects may also recognize the consensus KBS. Previous genetic analyses in some insects demonstrated that Kr-h1 represses BR-C and/or E93 (25,35,36). Therefore, the function and mechanism by which Kr-h1 represses the transcription of E93 and/or BR-C are essentially shared by a wide variety of insects.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations